COMPREHENSIVE SURGICAL APPROACH FOR DIFFERENT PHLEGMONS OF THE MAXILLOFACIAL REGION (Archive of Conferences, 2021)
Over the past few years, the most common form of pyoinflammatory diseases of the maxillofacial region (CMP) has been odontogenic phlegmon. At the same time, many authors note an increase in the number of patients with this pathology, indicating the severity of the course of the disease, an increase in the frequency of atypical forms, including those characterized by a fulminant course